2020
DOI: 10.1371/journal.pone.0241925
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning approach to predict pancreatic islet grafts rejection versus tolerance

Abstract: The application of artificial intelligence (AI) and machine learning (ML) in biomedical research promises to unlock new information from the vast amounts of data being generated through the delivery of healthcare and the expanding high-throughput research applications. Such information can aid medical diagnoses and reveal various unique patterns of biochemical and immune features that can serve as early disease biomarkers. In this report, we demonstrate the feasibility of using an AI/ML approach in a relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Notably, predictions of the same functions, pathways, and networks were consistently made at several, less stringent, cutoff values in our current dataset. We recently showed that the prediction accuracy in a small dataset was higher based on complete peak patterns in whole electropherograms rather than a few discriminative peaks selected based on significance, despite the potentially higher noise (non-significantly different peaks) in the compared electropherograms [ 94 ]. For instance, inflammatory response, proliferation of immune cells including T-lymphocytes, especially CD4+, and their increased motility, and the activation of macrophages and ROS generation were only indicated at the three lower cutoff values ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, predictions of the same functions, pathways, and networks were consistently made at several, less stringent, cutoff values in our current dataset. We recently showed that the prediction accuracy in a small dataset was higher based on complete peak patterns in whole electropherograms rather than a few discriminative peaks selected based on significance, despite the potentially higher noise (non-significantly different peaks) in the compared electropherograms [ 94 ]. For instance, inflammatory response, proliferation of immune cells including T-lymphocytes, especially CD4+, and their increased motility, and the activation of macrophages and ROS generation were only indicated at the three lower cutoff values ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Capitalizing on these technical capabilities of the ACE-platform, we previously identified significant changes in the local proteome and metabolome in association with intraocular islet allografts rejection [25,26]. Here, we further examine specific changes in local metabolites and proteins involved in immunometabolism in the context of immune tolerance.…”
Section: Introductionmentioning
confidence: 94%
“…The migration of each peak, which correspond to a putative metabolite, is dictated by the electro-osmotic properties of the metabolite [27,28]. Therefore, peaks in different EPGs with the same migration time likely correspond to the same metabolite [26]. The first group of peaks (group A) migrated between 6 and 15 min.…”
Section: Patterns Of Electropherograms Generated In Aqueous Humor Samples During Rejection Versus Tolerance Are Significantly Differentmentioning
confidence: 99%
“…Microliter-size aqueous samples can be obtained in the immediate vicinity of the engrafted tissue, allowing for the analysis of islet-related metabolites and proteins. In particular, this strategy has been used with the aim to define early predictive markers of type 1 diabetes by detecting changes in the metabolic profile (50), and to predict the risk of allograft rejection to allow for a timely therapeutic intervention (51,52). As a whole, these methodologies using the ACE platform are perfectly suited for the study of islet plasticity in health and disease under in vivo conditions.…”
Section: The Ace As a Transplantation Site And The Cornea As A Natural Body Window For Imaging Pancreatic Islet Cellsmentioning
confidence: 99%